PENGARUH PERTUMBUHAN PENDAPATAN ASLI DAERAH DAN PERTUMBUHAN BELANJA MODAL TERHADAP FISKAL STRESS DI KOTA SAMARINDA - Winda Fitryani; Juliansyah Roy; Muliadi Muliadi (Jurnal Ilmu Ekonomi Mulawarman (JIEM), 2019)
The purpose of this study was to determine 1) the effect of the growth of local revenue on the physical stress of Samarinda City 2) the effect of the growth of capital expenditure on fiscal stress in Samarinda City. Using the Multiple Linear Regression model. This study uses secondary data obtained from the Revenue Service and the Statistical Center of Samarinda City.            The results show that significant regional income growth affects Fiscal stress in the Samarinda City Government. While the Capital Expenditures Growth did not have a significant influence on Fiscall Stress in the City Government of Samarinda. And simistantly Fiscal Stress is influenced by the growth of the original regional income, and the growth of capital expenditure            This shows that the decrease in the PAD ratio that occurred in 2013 and 2015 in the City of Samarinda Government against total revenue is a reflection that PAD has not been able to dominate the total revenue component of regional revenue. And there is a negative relationship between capital expenditure growth and fiscal stress. The growth rate of regional capital expenditure in 2015 has actually declined when the region experiences increasingly high fiscal pressure.